The Effect of Profitability, Leverage, Operating Cash Flow, and Firm Size on Tax Avoidance: The Moderating Role of Institutional Ownership - Amelia Sasi Kirana; Maryati (Danadyaksa: Post Modern Economy Journal, 2026)
This study investigates the effect of profitability, leverage, operating cash flow, and firm size on tax avoidance, with institutional ownership serving as a moderating variable. The research focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative research approach was employed using secondary data obtained from companies’ annual reports and audited financial statements. The sample was selected through purposive sampling, resulting in 35 mining companies with a total of 175 firm-year observations. Data analysis was conducted using panel data regression and Moderated Regression Analysis (MRA) with EViews 12 software. The empirical findings reveal that profitability and leverage have a positive and statistically significant effect on tax avoidance, indicating that more profitable and highly leveraged firms are more likely to engage in tax avoidance strategies. Conversely, operating cash flow and firm size exhibit negative but statistically insignificant effects on tax avoidance. The moderation analysis demonstrates that institutional ownership significantly moderates the relationships between profitability, operating cash flow, and firm size with tax avoidance, suggesting that institutional investors strengthen corporate oversight and influence managerial tax-related decisions. However, institutional ownership does not significantly moderate the relationship between leverage and tax avoidance. These findings highlight the importance of institutional ownership as an effective corporate governance mechanism in reducing agency problems and shaping corporate tax planning behavior. This study contributes to the accounting and taxation literature by providing empirical evidence on the moderating role of institutional ownership in the relationship between firm-specific characteristics and tax avoidance practices in Indonesian mining companies.